Flood Disaster Risk Reduction Strategies in Urban Area, Bulukumba Regency - Andi Idham Asman; Harry Hardian Sakti; Dzulqarnain Aras; Nurul Wahyuni; Farhan Aldiansyah (Faculty of Engineering, Andi Djemma University, 2023)
Flood is a disaster that often occurs in big cities in Indonesia, caused by the high density of buildings and the unpreparedness of infrastructure to adapt. Urban Areas of Bulukumba Regency (UABR) is one of the centers of urban areas that has experienced flooding in recent years. The urban area ofBulukumba Regency is a downstream area of the Bialo Watershed whose upstream area is also in the Bantaeng Regency area. Rapid urban development has resulted in a change in land cover to become built-up land so that catchment areas are narrower in the middle and downstream zones, as well as changes in vegetation in the upstream zone which has received land conversion from forest areas to plantation areas. In addition to the potential for flooding due to river flow, the urban area of Bulukumba also has the potential for flooding due to sea tides or tidal floods. The high level of hazard flood potential has not been followed up with sustainable flood management based on disaster risk reduction in the UABR. Based on this, it is necessary to study the level of risk of flooding in the Urban Area of Bulukumba Regency and an appropriate strategy to reduce the risk of flooding in the Urban Area ofBulukumba. The aim of this research is; (1) identify the level of risk of flooding in the UABR; and (2) formulate an appropriate strategy as an effort to reduce the risk of flood disaster in the UABR. The research approach used is the mixed method, with the analytical method used for data processing in the form of risk analysis, spatial analysis namely overlay analysis using GIS software and qualitative descriptive in formulating strategies. The results of this study are a map of the level of flood disaster risk and recommendations for flood risk reduction strategies in the UABR.